2010
DOI: 10.1007/s00417-010-1519-2
|View full text |Cite
|
Sign up to set email alerts
|

Normal standards of eye projection in Turkish children 6 to 17 years of age

Abstract: Age- and gender-specific references for exophthalmos provide important information both for the clinical decision-making process, and screening in the diagnosis of abnormal or pathological conditions which result in exophthalmos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Comparing Caucasian race of American children and adolescents group with our children and adolescents eye proptosis measurements results are quite similar 17 . The ocular protrusion of children in our recent study tends to have higher exophthalmometric readings than those reported in Turkish, Indian children and adolescents 12, 15, 16. In an Indian juvenile population, the normal proptosis values were observed to be lower than other races studied 12 .…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Comparing Caucasian race of American children and adolescents group with our children and adolescents eye proptosis measurements results are quite similar 17 . The ocular protrusion of children in our recent study tends to have higher exophthalmometric readings than those reported in Turkish, Indian children and adolescents 12, 15, 16. In an Indian juvenile population, the normal proptosis values were observed to be lower than other races studied 12 .…”
Section: Discussionsupporting
confidence: 77%
“…According to previous studies, in the majority of under-age persons from different ethnic origins, there was no significant difference between eyes and the relative protrusion value was below than 2 mm 5, 7, 12, 13, 14, 15, 16. Kara study also found that the mean relative protrusion was 0.43 mm for girls and 0.48 mm for boys 15 . Therefore, the relative ocular protrusion value of up to 2.0 mm in the absence of other pathological findings could be considered as normal.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Bu çal›flmada, ülkemizde ilk kez 6-18 yafl grubundaki beden ya¤ yüzdesi persentilleri ve ekzoftalmi referans de¤erleri hesapland›. [14,15] Obezitede metabolik ve kardiyovasküler hastal›lar aç›s›ndan BKI'nin yan›nda bel çevresinin de de¤erlendirilmesi gere¤i art›k yayg›n kabul görmektedir. [16,17] Bel çevresi beden üst k›sm›nda biriken ya¤, metabolik ve kardiyovaskü-ler hastal›klar aç›s›ndan önemli bir tan› ve prognoz belirleyicisidir.…”
Section: -18 Yafl çOcuk Ve Ergenlerde Büyüme E¤rilerinin Belirlenmesiunclassified